Pengaruh Rasio Keuangan terhadap Perubahan Laba pada Perusahaan Telekomunikasi yang Terdaftar di Bei Tahun 2019-2023 - Rahmiani Rahmiani; Sitti Hasbiah; Andi Mustika Amin; Nurman Nurman; Annisa Paramaswary Aslam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aimed to determine and analyze the influence of financial ratios on profit changes in telecommunications companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The financial ratios used in this study encompass four main groups: liquidity ratios, solvency ratios, activity ratios, and profitability ratios. This study employed a quantitative approach with an associative nature because it attempted to examine the relationship and influence between these financial variables on profit changes. The population in this study comprised all telecommunications companies listed on the IDX, while the sample selection was conducted using a purposive sampling technique with specific criteria, resulting in 15 eligible companies. The research data were then analyzed using panel data regression using EViews 12 software, with the best model selected being the Random Effect Model (REM). The results showed that simultaneously, liquidity, solvency, activity, and profitability ratios significantly influenced profit changes, thus concluding that the company's overall financial performance plays a significant role in determining the dynamics of profit generated. However, partial test results showed that the influence of each ratio was different. The solvency ratio has a significant negative effect on profit changes, indicating that the higher a company's debt level, the greater the risk of profit decline. Conversely, the profitability ratio has a significant positive effect, confirming that a company's ability to generate net profit is a major factor in increasing profit changes. Meanwhile, the liquidity ratio and activity ratio were not shown to have a significant effect on profit changes, indicating that short-term liquidity and operational efficiency are not sufficient to be the primary determinants in driving profit changes in the telecommunications sector.